Brain tumors risk factors - current state of knowledge review - Zygmunt Siedlecki; Małgorzata Szafrańska; Emilia Główczewska-Siedlecka; Maciej Śniegocki (Kazimierz Wielki University, 2021)
Brain tumors cause widespread apprehension in society, associated with poor prognosis and death. Laymen most often associate them with glioblastoma multiforme which is in fact the most common malignant primary brain tumor (formerly it was considered the most common primary brain tumor, now it is thought that meningiomas are the most common). The interest of both the public and physicians is aroused by potential brain tumors risk factors. The only evidence based risk factor is ionizing radiation of head and neck. Other risk factors are also under consideration, however are not conclusive and different studies give different results. Given the widespread apprehension of brain tumors, knowledge of the risk factors seems obvious. In this manuscript, we have reviewed the current state of knowledge aboutf risk factors based on research. They confirm that apart from ionizing radiation, the existence of other risk factors is considered: cell phones, electromagnetic field, occupational exposure to raw meat, viruses. However, all these risk factors are not confirmed by reference results.